(untitled) (Proceedings of the International Conference on Public Health, 2024)
This study investigates the psychosocial health of Thai surrogates with a focus on advancing the development of surrogacy health promotion and policy at both national and international levels. Employing semi-structured telephonic interviews with fifteen Thai women who had served as surrogates within the previous seven years, the research identified four thematic dimensions—mental, environmental, social, and spiritual health—unveiling various aspects of surrogates’ psychosocial well-being. Despite generally positive sentiments and the absence of perceived health risks, the study uncovered a noticeable impact on psychosocial health outcomes. The conclusion underscores the complexity of surrogates’ psychosocial well-being, emphasizing their understanding of roles, spiritual fulfillment, and familial support. Additionally, it sheds light on unforeseen consequences of surrogacy bans, advocates for regulatory reform, and stresses the imperative for international cooperation to safeguard the well-being of all involved in surrogacy.